Three Phase Measurements of Nonwetting Phase Trapping in Unconsolidated Sand Packs - Al-Mansoori, S.; Iglauer, Stefan; Pentland, C.; Blunt, M. (SOC PETROLEUM ENG, 2009)
We perform a series of experiments in water-wet sand packs to measure the trapped saturations of oil and gas as a function of initial saturation. We start with brine-saturated columns and inject octane (oil) to reach irreducible water saturation followed by displacement by air (gas) from the top, allowing oil and air to drain under gravity for different amounts of time, then finally brine is injected from the bottom to trap both oil and gas. The columns are sliced and a sensitive and accurate measurement of saturation along the column is made using gas chromatography. The maximum residual gas saturation is over 20%, compared to 14% for two-phase flow (Al Mansoori et al. 2009). For lower initial gas saturation, the amount of trapping is similar to that reached in an equivalent two-phase experiment.We also find that the amount of oil trapped is insensitive to either the initial gas saturation or the amount of gas that is trapped. More oil is trapped than would be predicted from an equivalent two-phase system, although the trapped saturation is never larger than the maximum reached in two-phase flow (around 11%) (Pentland et al. 2008). These initially surprising results are explained in the context of oil layer stability and the competition between snap-off and piston-like advance. In unconsolidated two-phase water-wet systems, displacement is principally by cooperative piston-like advance with relatively little trapping, whereas in consolidated media snap-off is generally more significant. However, during three-phase waterflooding, oil layer collapse events rapidly trap the oil which acts as a barrier to direct water-gas displacement, except by snap-off, leading to enhanced gas trapping.